Cost-benefits of incorporating levosimendan into cardiac surgery practice: German base case. (3rd May 2016) - Mardiguian, Silvy; Kivikko, Matti; Heringlake, Matthias; Smare, Caitlin; Bertranou, Evelina; Apajasalo, Marjo; Pollesello, Piero
Abstract: Objective: To evaluate the cost-benefit of using levosimendan compared with dobutamine, in the perioperative treatment of patients undergoing cardiac surgery who require inotropic support. Methods: A two-part Markov model was designed to simulate health-state transitions of patients undergoing cardiac surgery, and estimate the short- and long-term health benefits of treatment. Hospital length of stay (LOS), mortality, medication, and adverse events were key clinical- and cost-inputs. Cost-benefits were evaluated in terms of costs and bed stays within the German healthcare system. Drug prices were calculated from the German Drug Directory (€/2014) and published literature, with a 3% annual discount rate applied. The base case analysis was for a 1-year time horizon. Results: The use of levosimendan vs dobutamine was associated with cost savings of €4787 per patient from the German hospital perspective due to reduced adverse events and shorter hospital LOS, leading to increased bed capacity and hospital revenue. Limitations: A pharmacoeconomic calculation for the specific situation of the German healthcare system that is based on international clinical trial carries a substantial risk of disregarding potentially relevant but unknown confounding factors (i.e., ICU-staffing, co-medications, standard-ICU care vs fast-tracking, etc.) that may either attenuate or increase the outcome pharmacoeconomic effects of a drug; however, since these conditions would also apply for patients treated with comparators, their net effects may not necessarily influence the conclusions. Conclusions: The use of levosimendan in patients undergoing cardiac surgery who require inotropic support appears to be cost-saving. The results of the analysis provide a strong rationale to run local clinical studies with pharmacoeconomic end-points which would allow a much more precise computation of the benefits of levosimendan.